Soft Skills and Psychological Well-being: A Study on Italian Rural and Urban NEETs - Mauro Ellena, Adriano; Marta, Elena; Simões, Francisco; Fernandes-Jesus, Maria; Petrescu, Claudia (Calitatea Vieții, 2021)
Soft skills retain a certain importance in fully understanding the NEET phenomenon: however, only few researchers have focused on them specifically. The aim of this work is two-fold: a) to detect the differences in terms of soft skills and psychological well-being between urban and rural NEETs; and b) to evaluate which of the soft skills analysed may be predictors of psychological well-being. A sample of young 6998 18−34 years old representative of the Italian population was used. Although gender and educational attainment play a key role in determining NEET status, the degree of urbanisation must be considered because it appears to influence the well-being and perceived soft skills of a group of NEETs. The present study shows that females with low educational attainment residing in rural areas have lower levels of well-being than females with low educational attainment residing in urban areas. A similar influence exists in relation to one particular soft skill: positive vision. Furthermore, soft skills predict psychological well-being wherein degree of urbanisation and gender seems to play a determining role. Policies should, therefore, consider these issues in their design and implementation phases.